Astragalus membranaceus Additive Improves Serum Biochemical Parameters and Reproductive Performance in Postpartum Dairy Cows - Huang, Yinghao; Yan, Qi; Jiang, Maocheng; Guo, Sheng; Li, Huiwei; Lin, Miao; Zhan, Kang; Zhao, Guoqi; Duan, Jinao (Frontiers in Veterinary Science, 2022)
In this experiment, astragalus membranaceus (AM) based feed additives were used to feed postpartum dairy cows, aiming to help dairy cows recover rapidly in the postpartum period and enhance the immune function and breeding efficiency of dairy cows. The experiment lasted 21 days and was divided into AM group and CON group. The AM group was fed 675 g per day.The experimental results showed that compared with the CON group, the breeding interval of the AM group of dairy cows had a tendency to shorten (0.05 < P < 0.1). The results of Plasma viscosity (PV), Plasma fibrinogen (FIB), The red cell aggregation index (TRCAI), Calcitonin (CT), IgM and Luteinizing hormone (LH) showed that the AM group interacted with time and treatment (P < 0.05). The experimental results showed that feeding AM feed additives had positive effects on wound recovery, promoting immune function, regulating endocrine and improving breeding efficiency of dairy cows in the postpartum period.